Effectiveness of coordination in humanitarian water, sanitation, and hygiene (WASH) response: evidence from a mixed-methods evaluation of outcomes and outputs across five national coordination platforms - Nguyen, Daniel; Heylen, Camille; Cunningham, Cora; Salagnac, Aliocha; Ramos, Monica; Lantagne, Daniele (Tufts University Tisch Library, 2026)
Keywords: Complex humanitarian emergency, Cluster approach, Crisis, Disasters, Emergency, Environmental health, Non-governmental organizations; Springer Open.